Upgrade pacemaker to CRT: predictors and the importance of LVEF. (19th May 2022) - Silva, BV; Silverio Antonio, P; Couto Pereira, S; Alves Da Silva, P; Brito, J; Garcia, B; Oliveira, C; Martins, AM; Nunes Ferreira, A; Magalhaes, A; Cristina, H; J Pinto, F; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Nowadays 10-15% of CRT implantaon is upgrading from paents (pts) with pacemaker (PMK) who develop reduced LVEF and worsening symptoms from HF. There are few retrospecve studies showing some predictors of pts with single or dual chamber PMK that may need upgrade to CRT, but it is not completely established which pts may benefit the most. Purpose: To identify predictors at follow-up of upgrading pacemaker to CRT in a population with pacemaker implantation. Methods: Single center case-control study of pts that performed upgrading to CRT-pacemaker (CRT-P) in our hospital. We excluded pts that performed upgrade to CRT-D. We compare to a PMK populaon matched to age at implantaon and cause of PMK implantaon. Demographic, clinic and electrocardiographic (ECG) data were considered at baseline. Echocardiographic evaluation was performed before pacemaker/CRT upgrading implantaon and at follow-up. Predictors of upgrading were evaluated by the Cox regression. Prognosc impact of LVEF was evaluated as upgrading to CRT-P by Kaplan-Meier curves. Results: We included 71 pts that performed CRT-P upgrade (mean age 77±10; 49, 6% male, mean LVEF before PMK 54.9±9.2%) and 71 pts with pacemaker implantaon (mean age 78 ± 11; 50, 4% male; mean LVEF 60.9±7.2%). The clinical characteriscs, ECG and echocardiographic were similar between pacemaker and CRT-P-upgrade, except atrial fibrillaon being more prevalent in PMK group (57.5% vs 42.5% p=0.039). Mortality was not different duringfollow-up between the two groups. In univariate analysis, QRS duraon (PMK: 115ms vs upgrade CRT-P: 132 ms, p=0.038), LVEF (PMK: 60.9% vs upgrade CRT-P: 54.9%, p=0.002) and LV end-diastolic diameter (LVEDD) (PMK: 48.9.4 ± 6.6mm vs upgrade CRT-P: 56.4 ± 6.6mm, p=0.001), LV end-sistolic diameter (LVESD) (PMK: 29.5 ± 6.5mm vs upgrade CRT-P: 37.9 ± 9 mm, p=0.006) were associate to upgrading to CRT. In our population, the unique independent predictor was lower LVEF(Long Rank 6.108, p=0.013) – Figure 1. The best LVEF cut- off to predict upgradingto CRT was 55% (AUC 0.954, sensitivity 64%, specificity 84%) – Figure 2. Conclusion: In our populaon of CRT upgrading pts, a broad QRS duraon, lower LVEF and a higher LVEDD and LVESD were associated to upgrade to CTR-P. We try to establish a new value for LVEF that could lead to upgradingto CRT-P, and maybe the classical cut-off of 50% should be reviewed.